2022
DOI: 10.1111/ahe.12861
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, histology, development and functions of Ossa cordis: A review

Abstract: This systematic review highlights the similarities and variations in Ossa cordis prevalence, histology and anatomical location between differing veterinary species and in humans. In addition, it also identifies associated factors such as aging and cardiovascular disease for each species in relation to functional roles and developmental mechanisms that these bone structures may play. The potential functions of Ossa cordis are presented, ranging from aiding cardiac contraction and conduction, providing cardiac s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
1
8
0
2
Order By: Relevance
“…It is of interest that Ossa cordis have not yet been reported, despite extensive cardiac explorations, in the closely related alpaca ( Vicugna pacos ) and llama (Lama glama), which also resides in the Artiodactyla order, Tylopoda suborder, within the Camelidae family (Mattoon et al, 2001 ; Perez et al, 2018 ). This is especially interesting given that the Old World camels and New World camels generally have hearts more similar to each other than Ruminantia , yet many ruminants have Ossa cordis (Best et al, 2022 ; Perez et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is of interest that Ossa cordis have not yet been reported, despite extensive cardiac explorations, in the closely related alpaca ( Vicugna pacos ) and llama (Lama glama), which also resides in the Artiodactyla order, Tylopoda suborder, within the Camelidae family (Mattoon et al, 2001 ; Perez et al, 2018 ). This is especially interesting given that the Old World camels and New World camels generally have hearts more similar to each other than Ruminantia , yet many ruminants have Ossa cordis (Best et al, 2022 ; Perez et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ossa cordis can expand into the trigone(s) between the atrioventricular openings and therefore the aortic opening. Previous work in differing species has shown that Ossa cordis dextrum are more common, and are usually larger, than those on the left (Best et al, 2022 ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…У хижаків домінує кулеподібна або конусовидно-еліпсоподібна форми. Згідно літературних джерел, у собаки, залежно від їх породних властивостей, зустрічається еліпсоподібна (43 %), конусоеліпсоподібна (24 %), еліпсо-куляста (26 %) та куляста (7 %) форми (Gómez-Torres et al, 2021;Best et al, 2022).…”
Section: результати та їх обговоренняunclassified